About characterizing monotonicity ofnonsmooth continuous mappings - Nguyễn, Huy Chiêu (Trường Đại học Đà Lạt, 2012)
This note is a re-edited form of our presentation at the 8th VietnamKorea Workshop on Mathematical Optimization Theory and Applications, December 8-10, 2011, University of Dalat, Dalat, Vietnam. It contains Borne our recent results on characterizing the monotonicity of nonsmooth continuous mappings by using coderivatives introduced by Mordukhovich in 1980 [Soviet Math. Dokl. 22 (1980), 526-5301. While moat of them were published on Taiwanese Journal of Mathematics 16 (2012), 353 - 365, few results are new.